2021
DOI: 10.1088/1361-6528/ac1d05
|View full text |Cite
|
Sign up to set email alerts
|

Layer exchange synthesis of multilayer graphene

Abstract: Low-temperature synthesis of multilayer graphene (MLG) on arbitrary substrates is the key to incorporating MLG-based functional thin films, including transparent electrodes, low-resistance wiring, heat spreaders, and battery anodes in advanced electronic devices. This paper reviews the synthesis of MLG via the layer exchange (LE) phenomenon between carbon and metal from its mechanism to the possibility of device applications. The mechanism of LE is completely different from that of conventional MLG precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 152 publications
0
17
0
Order By: Relevance
“…We found that high-quality MLG was formed from low-density a-C sputtered under high-pressure conditions. This is because poor crystallinity is preferred for the initial a-C in LE, which is consistent with the LE of semiconducting materials such as Si. Moreover, O in the a-C film suppresses the diffusion of C atoms into Ni, resulting in a lower nucleation frequency of MLG and the formation of larger MLG domains. In Figure d, the lowest annealing temperature at which LE occurred in 10 min of annealing is plotted as a function of P a‑C , which shows that the lowest LE temperature strongly depends on P a‑C .…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…We found that high-quality MLG was formed from low-density a-C sputtered under high-pressure conditions. This is because poor crystallinity is preferred for the initial a-C in LE, which is consistent with the LE of semiconducting materials such as Si. Moreover, O in the a-C film suppresses the diffusion of C atoms into Ni, resulting in a lower nucleation frequency of MLG and the formation of larger MLG domains. In Figure d, the lowest annealing temperature at which LE occurred in 10 min of annealing is plotted as a function of P a‑C , which shows that the lowest LE temperature strongly depends on P a‑C .…”
Section: Resultsmentioning
confidence: 58%
“…42 These results indicate that LE occurred in all samples and that MLG was formed on the SiO 2 substrate after annealing at 800 °C. 37 Figure 2c shows the intensity ratio of the G to D peaks (I G /I D ) in the Raman spectra, which is This I G /I D ratio behavior suggests an enlargement of the MLG domain size. We found that high-quality MLG was formed from low-density a-C sputtered under high-pressure conditions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We synthesized multilayer graphene (graphite thin films) by adapting LE to carbon. The anode properties of graphite thin films are strongly dependent on the LE conditions, and our group had demonstrated anode capacities comparable to those of bulk graphite by controlling them. , In this study, we controlled the crystallinity and structure of Si by modulating the growth temperature and film thickness ratio in the Al-induced LE and investigated the effects of the LE conditions on the anode properties. Furthermore, a fine nanostructure was formed using EE.…”
Section: Introductionmentioning
confidence: 99%
“…Although graphite is generally synthesized at high temperatures (> 2000 °C), we achieved low-temperature synthesis of graphite thin films (i.e., multilayer graphene (MLG)) on plastic films (polyimide: heat resistance of up to 400 °C) via metal-induced layer exchange (LE) 4 . In LE, an amorphous layer crystallizes through LE between the amorphous layer and metal catalyst layer 5 , 6 . LE will be suitable for microfabrication of devices because it can synthesize crystalline thin films with controlled thicknesses on arbitrary substrates at low temperatures 7 , 8 .…”
mentioning
confidence: 99%